Archiv Bibliographia Judaica - Deutschsprachiges Judentum Online Historische Kontexte und Einführung in die Datenbank - Burdorf, Dieter (De Gruyter, 2022)
The Bibliographica Judaica Archive in Frankfurt am Main has spent decades gathering the biobibliographical data of about 20,000 German Jewish personalities. This unique data stock is now available on De Gruyter's ABJ - German Judaism Online database. This supplementary volume provides an introduction to the history of the archive's origins and to its significance in the history of scholarship.